Patterns of Hazardous Drinking and Socio Demographic Characteristics among Selected Tribal Community, in Bangladesh - Farah, Shayela; Karim, Mohoshina (Journal of Diseases, 2016)
Tribal and minority populations’ square measure progressively exposed to risk factors as a results of urbanization. The study was conducted within the Rakhain community in Cox’s Bazar district, Bangladesh, with the aims of deciding the patterns of unsafe drinking and their socio demographic characteristics. This cross-sectional study was done among 287 Rakhain people. Informations were collected by face to face interview using pretested structured form. Seriously sick, lunatic person and who weren't interesting to involve were excluded from the study. Substance use was significantly high among the age group of 35-44 years. Their mean age was 40.66 (±11.275) years. Majority of the respondents was male 148(52%), married 222(77.4%) and educated up to primary level 179(62.4%). The very best proportion 68(23.7%) of the respondents were housewife and day labourer and lowest was jobless 26(9.1%). Their average monthly family financial gain was 17874.56 (±7208.553) Taka. More than fifty percent Rakhain consumed beer as hazardous drinking. Statistically important association was found between their pattern of drinking and socio-demographic characteristics (p <0.001). Hence improvement of educational and employment status of tribals strongly needed. It’s dreadfully necessary of interventions to promote knowledge, awareness, and health skill among the ethnic Rakhain tribes to guide a healthy life.